THE EFFECTIVENESS OF A TRAINING PROGRAM BASED ON TRAINING AND PRACTICE STRATEGY IN DEVELOPING DIWANI CALLIRAPHY SKILLS AMONG FEMALE STUDENTS OF THE INSTITUTE OF FINE ARTS (Journal of the College of Basic Education, 2022)
The rapid change in all areas of life is the distinguishing feature of the current era, as the circumstances of the era require the search for new ways and various ways to open the way for our students to acquire the knowledge and skills necessary to keep abreast of developments and developments. Educational scientists in understanding the role of natural sciences in the use of scientific techniques in education as new educational means, as it made education enter the field of modern sciences and prepare educational and training programs that suit the actual needs of each category of society. With technological progress, the importance of using new methods and methods in education has increased.Thus, the problem of the current research focuses on the lack of use of important topics in the artistic life of the learners, where the subject of Arabic calligraphy - Diwani calligraphy, as it is one of the basic materials that enter into building and consolidating the artistic work as it provides the learner with technical skills and experiences with a historical heritage and linking it to development. Therefore, teaching this subject is still captive to the use of traditional teaching methods that emphasize the formal aspects without involving learners and their interaction in educational situations. It also depends on traditional assessment methods that cannot achieve the learner's goals. In addition to using old technical means that do not arouse the desires of learners and increase their effectiveness towards achieving mastery of performance with a high level of technical skills for the technical subject (Arabic calligraphy - Diwani). In order to verify the research problem, the researcher conducted a questionnaire for the students of the Institute of Fine Arts, and the results of the survey showed the presence of several weaknesses and shortcomings in performance, and accordingly, the axes that needed to be addressed were diagnosed by searching for modern methods for teaching Arabic calligraphy and preparing training plans for the rules of writing (Diwani script) according to The training and practice strategy adopts the principle of simplifying the study material, and the learner feels that the process of learning the Diwani script is a very simple, uncomplicated and not difficult process. The search was aimedBuilding a training program based on training and practice strategy to acquire Diwani calligraphy skills for female students of the Institute of Fine Arts.Knowing the effectiveness of a training program based on training and practice strategy in developing Diwani calligraphy skills for female students of the Institute of Fine Arts in its knowledge and skill dimensions by applying it to a sample of students of the Institute of Fine Arts.In order to achieve the research objectives, the researcher put (4) null hypotheses (2) before and (2) after.The researcher used the experimental method, as he chose the experimental design with two equal and independent groups (experimental and control) with two tests, the pre and posttests, to achieve the objectives and hypotheses of the research. 25 female students for the academic year ( 2021-2022 AD) and (5) of them were excluded for not complying with attendance, and thus the number became (20) students, and they were randomly distributed to be two groups, the first experimental consisting of (10) students who studied in the training program, and the second consisting of ( 10) Female students studied the subject in the usual way.The statistical treatments used by the researcher were:1- The Mann Whitney test for two independent samples.2- Wilcoxon test.3- Equation of difficulty and discrimination coefficient.4- (Holstey) equation of apparent honesty. The results of the research were that there was a significant difference at the level (0.05) between the mean scores of the students of the two experimental groups who studied the material in the training program and the control group who studied the material in the usual way in the post-test (cognitive and skill) and for the benefit of the experimental group. This development is attributed to the effectiveness of the training program.The researcher made several recommendations, including:Approval of the training program (the effectiveness of a training program based on the strategy of training and practice in developing Diwani calligraphy skills among female students of the Institute of Fine Arts) for its effectiveness in providing the students with the information and skills needed to develop Diwani calligraphy skills.The possibility of benefiting from the training program in the institutions and institutes that study this subject or its equivalent. The researcher suggested conducting several studies, including:Building a training program in developing the cognitive, skill and behavioral aspects in Al-Jali Diwani script.Building an educational portfolio in mastering the skills of Diwani calligraphy among students of the Calligraphy and Decoration Department at the College of Fine Arts.Diwani calligraphy and its use in implementing contemporary plastic works among students of the Department of Art Education, College of Basic Education.The researcher suggested conducting several studies, including:Building a training program in developing the cognitive, skill and behavioral aspects in Al-Jali Diwani script.Building an educational portfolio in mastering the skills of Diwani calligraphy among students of the Calligraphy and Decoration Department at the College of Fine Arts.Diwani calligraphy and its use in implementing contemporary plastic works among students of the Department of Art Education, College of Basic Education.